Stable electron donor-acceptor nanohybrids by interfacing n-type TCAQ with p-type single-walled carbon nanotubes - Romero, Carlos; Garcia, Raul; Angeles Herranz, Maria; Rodriguez-Perez, Laura; Sanchez-Navarro, Macarena; Rojo, Javier; Martin, Nazario; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2013)
Tuning the electronics of nanotubes: Electron-accepting 11,11,12,12-tetracyano-9,10-anthraquinodimethane (TCAQ) nanotweezers endowed with a carboxylic acid-containing dendrimeric moiety form exceptionally stable n-/p-type dispersions with single-walled carbon nanotubes (SWCNTs) in water. Upon photoexcitation, the nanohybrids undergo a less common electron transfer from the SWCNTs to the TCAQ nanotweezers (see picture). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.